Digestibility of nutrients, balance of nitrogen and growth performance in dairy heifers fed mixed forage diets - RADOTRA, SUDESH; KATOCH, B S; SHARMA, V K (The Indian Journal of Animal Sciences, 2014)
Guinea grass (panicum maximum Jacq. PGG 9) and green panic grass (Panicum maximum Trichoglume HGP 2) were intercropped with ,oybcan with 3 replications and distributed in to 2 tn:atments, viz. T1-guinea grass -T2- soybean, and T2 green panic grass 1- soybean in completely randomized block design. Growing crossbred heifers (10; Jersey x Red Sindhi) of age 7-10 months with average body weight of 58-65 kg were divided on the basis of weight in above 2 treatment groups. The grasses along with soybean fodder were harvested fresh and evaluated ior green lind dry biomass production. The green and dry matter productions were 35.17±0.82 and 7.47±0.16 t/ha in guinea grass + soybean and 29.87±0.78 and 5.94±0.14 tiha in green panic grass + soybean respectively. The herbage mixtures were chaffed, mixed and fed to the animals. Chemical composition of the herbage mixtures, dry-matter intake, nutrients digestibility and growth performance in animals Were estimated. Guinea gross + soybean produced significantly (P